Archimandrite Leonid (Kavelin) and a collection of Slavic manuscripts in the library of St. Paul in Mount Athos monastery - A. A. Kashcheev (Библиосфера)
The article is devoted to bibliologic researches of the collection of Slavic manuscripts from the library of the Greek monastery of St. Paul in Mount Athos by Archimandrite Leonid (Kavelin). It tells about the history of the library of the Greek monastery of St. Paul. Through the study of various unpublished and published sources we were able to reestablish one of the moments of the history of the Serbian-Slavic manuscripts in this library, first presented in this article. A published source is a scientific work by Archimandrite Leonid (Kavelin) «Slavic-Serbian stocks in Mount Athos, in the monasteries Hilandar and St. Paul». Particular attention is paid to such a valuable source as Archimandrite correspondence with the inhabitants of Mount Athos monasteries, in particular, Hieromonk Macarius (Sushkin), librarian Azary (Poptsov), V. A. Dashkov - a director of Moscow Public Museum. The monastery library was visited by famous personalities in the history of book culture such as Archimandrite Porfiry (Uspensky), Archimandrite Antonin (Kapustin), archaeographer and Slavicist V. I. Grigorovich, English traveler and writer Robert Curzon. The article objective is to establish the role of Archimandrite Leonid (Kavelin) in saving Slavic manuscripts of St. Paul's monastery library through their acquisition of Rumyantsev Public Museum in Moscow. Unfortunately, due to a number of circumstances, the manuscripts were not acquired, and were burned at the beginning of the XX century.